Role of dimerization in yeast aspartyl-tRNA synthetase and importance of the class II invariant proline. - Eriani, G (1993)
Cytoplasmic aspartyl-tRNA synthetase (AspRS; EC 6.1.1.12) from yeast is, as are most class II synthetases, an alpha 2 dimer. The only invariant amino acid in signature motif 1 of this class is Pro-273; this residue is located at the dimer interface. To understand the role of Pro-273 in the conserved dimeric configuration, we tested the effect of a Pro-273-->Gly (P273G) substitution on the catalytic properties of homo- and heterodimeric AspRS. Heterodimers of AspRS were produced in vivo by overexpression of their respective subunit variants from plasmid-encoded genes and purified to homogeneity in one HPLC step. The homodimer containing the P273G shows an 80% inactivation of the enzyme and an affinity decrease for its cognate tRNA(Asp) of one order of magnitude. The P273G-mutated subunit recovered wild-type enzymatic properties when associated with a native subunit or a monomer otherwise inactivated having an intact dimeric interface domain. These results, which can be explained by the crystal structure of the native enzyme complexed with its substrates, confirm the structural importance of Pro-273 for dimerization and clearly establish the functional interdependence of the AspRS subunits. More generally, the dimeric conformation may be a structural prerequisite for the activity of mononucleotide binding sites constructed from antiparallel beta strands.